2019
DOI: 10.18517/ijaseit.9.6.10658
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV (DPP-IV) Inhibitory Activity of Ultrafiltration and Gel Filtration Fraction of Gelatin Hydrolyaste Derived from Bone of Fish for Antidiabetes

Abstract: Bioactive peptides have been investigated largely for many biofunctional properties. The aim of this research was to determine the inhibitory activity of ultrafiltration (UF) and gel filtration (GF) fractions of gelatin derived from bone of Pangasius catfish against dipeptidyl peptidase IV (DPP-IV). Previous studies have shown that gelatin from skins of salmon, hake, halibut, milkfish, tilapia and bone of pangasius catfish have the activity in DPP-IV inhibition. While, as inhibitor, most of previous and recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Moreover, TPH also showed a higher increase in the intracellular cAMP release as well as insulin secretion through the protein kinase A mechanism (Harnedy et al, 2018). Gelatin hydrolysate prepared from the bone of pangasius catfish using Flavourzyme was fractionated by ultrafiltration (3 kDa cutoff) membrane followed by gel filtration (Atma et al, 2019). Both fractions had DPP‐IV inhibitory activity, while UF fraction >3 kDa showed higher inhibitory activity than other fractions.…”
Section: Biological Activities Of Fph (In Vitro Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TPH also showed a higher increase in the intracellular cAMP release as well as insulin secretion through the protein kinase A mechanism (Harnedy et al, 2018). Gelatin hydrolysate prepared from the bone of pangasius catfish using Flavourzyme was fractionated by ultrafiltration (3 kDa cutoff) membrane followed by gel filtration (Atma et al, 2019). Both fractions had DPP‐IV inhibitory activity, while UF fraction >3 kDa showed higher inhibitory activity than other fractions.…”
Section: Biological Activities Of Fph (In Vitro Studies)mentioning
confidence: 99%
“…Recently, studies have shown that fish PH (FPH) derived from various parts of fish exhibits numerous bioactivities including antioxidant, antimicrobial, angiotensin-I converting enzyme (ACE) inhibition, calcium (Ca)-binding ability, antidiabetic, immunomodulatory, wound healing capacity, anticoagulant, anticancer, antifatigue, anti-aging, and neuroprotective effect (Altınelataman et al, 2019;Atma et al, 2019;Benjakul et al, 2018;Jiali Chen et al, 2020;Da Rocha et al, 2018;Hu et al, 2020;Kumar et al, 2019; J. K. Lee et al, 2019;Park & Jo, 2019). In this comprehensive review, sources, production, and purification of FPH or their derived peptides have been outlined.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, this process has been performed with different enzymes like alcalase, 19,20 trypsin, 21,22 or flavourzyme. 19,20,23 In some studies, the inhibitory effect of hydrolysates produced by a combination of multiple enzymes was investigated. 15,19,24 Another factor affecting the DPP-IV inhibitory activity in vivo is the further hydrolysis of peptides during gastrointestinal digestion, which can be simulated in vitro through a digest with pepsin, trypsin, and chymotrypsin.…”
Section: Introductionmentioning
confidence: 99%
“…In general, DPP-IV inhibitory peptides are released from proteins during hydrolysis. In previous studies, this process has been performed with different enzymes like alcalase, , trypsin, , or flavourzyme. ,, In some studies, the inhibitory effect of hydrolysates produced by a combination of multiple enzymes was investigated. ,, Another factor affecting the DPP-IV inhibitory activity in vivo is the further hydrolysis of peptides during gastrointestinal digestion, which can be simulated in vitro through a digest with pepsin, trypsin, and chymotrypsin. Although this process might be necessary for predicting how the food hydrolysate is taken up in the body and if it retains its inhibitory effect, it has only been performed in a limited number of studies. , …”
Section: Introductionmentioning
confidence: 99%